2021
DOI: 10.3390/su13105566
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Consumer Awareness and the Purchase of Eco-Friendly Vehicles: Textual Analysis of Korean Market

Abstract: Despite the positive outlook of various organizations on the prevalence of eco-friendly cars, Korea’s electric vehicle market is small, and growth is slow. To identify factors that hinder consumer awareness and the spread of eco-friendly vehicles, news articles and online postings on eco-friendly vehicles from 1 January 2006 to 31 December 2020 were collected and analyzed using text mining techniques. This study found that Korean consumers thought hybrid vehicles were fuel-efficient and quiet; however, there w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 25 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…Rombach and others found that the moral awareness of German cut-flower consumers' concern about labor and the environment affected their attention to fair trade as an attribute of cut flowers, which further affected their purchasing behavior [34]. Graham-Rowe [35] and Ju [36] explored the psychological obstacles of British and South Korean consumers to the adoption of electric vehicles, respectively. Kautish and others emphasized to pay attention to the influence of consumers' values and inner consciousness on their external reactions [37].…”
Section: Consciousnessmentioning
confidence: 99%
“…Rombach and others found that the moral awareness of German cut-flower consumers' concern about labor and the environment affected their attention to fair trade as an attribute of cut flowers, which further affected their purchasing behavior [34]. Graham-Rowe [35] and Ju [36] explored the psychological obstacles of British and South Korean consumers to the adoption of electric vehicles, respectively. Kautish and others emphasized to pay attention to the influence of consumers' values and inner consciousness on their external reactions [37].…”
Section: Consciousnessmentioning
confidence: 99%
“…With the concern for environmental conservation in the face of global warming and other climate change effects, and the increasing health consciousness in the aftermath of COVID-19 dominating the current global debate, governments and businesses alike are responding with environmental conservation strategies. The automobile industry, for instance, is geared towards the production of electric cars alongside internal combustion cars whose engines are powered by fossil fuels (Ju et al, 2021). Achtnicht (2012) as well as Gallagher and Muehlegger (2011) also note that car manufacturers are now producing cars that use less fuel and emit less emissions per mile to react to the call for environmental conservation.…”
Section: Introductionmentioning
confidence: 99%
“…The desire for environmentally friendly vehicles to run on alternate fuels is increasing significantly. As a result, the automobile industry is rapidly transitioning to something that is more environmentally sustainable, and the world's main automobile makers, as well as many countries, are attempting to gain a competitive advantage in electric vehicles and innovative technology [11]. The increased sales trends for EVs in the foreseeable future are possible.…”
Section: Introductionmentioning
confidence: 99%